2020
DOI: 10.1021/acs.chemmater.0c03661
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Thionated Naphthalene Diimides As Organic Cathodes for High Capacity Lithium Batteries

Abstract: Although naphthalene diimide (NDI) and its derivatives have been widely used for organic Li-ion batteries (OLIBs), they are limited by a low lithium uptake capacity and ambiguous lithiation mechanism. Herein, we report two isometric thionated-NDI cathodes (cis-2S and trans-2S) obtained by replacing O with S in the imide groups which improves the battery performance compared with parent NDI (P-NDI). Remarkably, the position of S atoms plays an important role as the potential plateau of cis-2S was 100 mV higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…Figure S1 shows the optimized geometry for this unit. We used molecular electrostatic potential (MESP) mapping, a widely employed tool for identifying ionic binding sites in organic charge storage materials. , Figure b shows the MESP map of a single T-DPP-T unit. Two MESP minima were found, one each in the vicinity of the two carbonyl-oxygen atoms on the DPP units, suggesting that these are the most favorable sites for cationic binding .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S1 shows the optimized geometry for this unit. We used molecular electrostatic potential (MESP) mapping, a widely employed tool for identifying ionic binding sites in organic charge storage materials. , Figure b shows the MESP map of a single T-DPP-T unit. Two MESP minima were found, one each in the vicinity of the two carbonyl-oxygen atoms on the DPP units, suggesting that these are the most favorable sites for cationic binding .…”
Section: Resultsmentioning
confidence: 99%
“…Discounting the side chains, which are needed only for enhanced solubility and associated film processability, the theoretical capacity of the polymer backbone alone amounts to ∼90 mAh/g for a single electron transfer reaction. This along with chemical approaches , to stabilize the second redox of the DPP unit could lead to capacities on the order of ∼180 mAh/g which is on par with some of the best intercalation electrode materials . Thus, careful molecular engineering to enhance electrochemical stability coupled with pruning the bulky side chains can lead to redox-active DPP-based polymers that offer necessary cycling stability at high energy densities required for advanced energy storage applications.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Zhang et al explored the impact of the partial thionation of carbonyl groups in naphthalene diimide on its electrochemical properties and highlighted the promise of the cis-type thionation outperforming the trans-type thionation. [7] Despite all these significant efforts, the basic principle of "the decrease in the molecular size increasing the redox activity (e.g., benzoquinone vs anthraquinone) and the probability of dissolution into electrolytes" is still applicable to organic cathode systems. Therefore, the problem of dissolution, particularly for small organic molecules, is yet to be fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dissolution of organic compounds is a crucial drawback that retards their practical applications, and hence, considerable studies have been conducted on the topic. [4][5][6][7][8] For instance, Lu et al reported cyclohexanehexone (C 6 O 6 ), which could store six Li atoms and exhibit an ultrahigh charge capacity of 902 mAh g −1 with an average voltage of 1.7 V versus Li/Li + at 20 mA g −1 . [4] They highlighted that the introduction of an ionic liquid with highly polar electrolytes could limit the dissolution of organic compounds, resulting in a high capacity retention of 82% even after 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The traditional lithium-ion battery has undergone limited large-scale development due to safety. [13][14][15] Based on the characteristics of high safety and long life, the ow battery stands out among many energy storage technologies, 16,17 which were considered very suitable for solar and wind power storage and transportation. [18][19][20] Among them, aqueous organic redox ow batteries (AORFBs) have become one of the best candidates for large-scale energy storage technology due to their abundant structures, cheap raw materials and high security.…”
mentioning
confidence: 99%